The Relationship Between Human Papillomavirus Knowledge and Health Literacy in University Students: Descriptive Correlational Study. - YORULMAZ DEMİR, Deniz S. (Turkiye Klinikleri Journal of Medical Sciences)
Objective: This study aimed to assess the level of knowledge about human papillomavirus (HPV), the health literacy status, and the HPV vaccination status of university students in Türkiye, and to examine the relationship between HPV knowledge and health literacy. Material and Methods: This study was based on a descriptive-relational design and involved 387 university students. The study utilized a descriptive characteristics questionnaire, HPV Knowledge Scale, and Health Literacy Scale to collect the research data. It also used descriptive analyses (number, percentage), chi-square analyses, and Pearson correlation analyses to evaluate the research data. Results: Of the participant students, 65.6% were women, 30.5% of their mothers had primary school education, and 34.4% had difficulty accessing health institutions. The study results indicated that 8.5% of the student's received education on HPV, 6.5% contacted healthcare professionals about HPV vaccines, and 7.2% and 10.1% received advice from their families and healthcare professionals, respectively, about the application of HPV vaccination. The average score of the students on the HPV Knowledge Scale was 6.06±7.09 (minimum: 0, maximum: 33), and 7.5% of the participant students reported receiving the HPV vaccine. The study also identified a positive and significant relationship between HPV knowledge and health literacy (r=0.113, p=<0.001). Conclusion: The students have a low level of knowledge about HPV, and only a small portion of them have received training on the subject. Given that HPV infection-related health problems, including cervical cancer, are a critical public health concern, this study recommends providing education and information about HPV infection prevention and HPV vaccine application.